A heat dissipation design strategy based on computational fluid dynamics analysis method for shunt active power filter. (July 2022) - Chen, Dongdong; Xiao, Long; Yan, Wenduan; Li, Yan; Guo, Yinbiao
Abstract: Aiming at the heat dissipation design problem of shunt active power filter, this paper proposes a computational fluid dynamics (CFD) simulation method of module flow–heat transfer coupling under forced air cooling. The power filter has carried out a detailed heat generation analysis, and given the analysis and simulation results, the heat dissipation system of the parallel active power filter is designed. The experimental results of the compensation performance prove that the designed modular system has an excellent dynamic, steady-state performance, and temperature rise. The experimental results are consistent with the simulation analysis, which demonstrates the effectiveness of the heat dissipation design of the parallel active power filter module proposed in this paper.